1965
DOI: 10.1007/bf01980335
|View full text |Cite
|
Sign up to set email alerts
|

Some new races ofPuccinia striiformis

Abstract: In the Netherlands in 1961 three new field races were found of Puccinia striiformis, the causal fungus of yellow rust on wheat. Two of these, viz. the 'Falco' race and the 'Opal' race, together with the already known 'Etoile de Choisy' race, constitute the so-called Nord-group of races, which is now deafly distinguished from the so-called Rubis-group. Most dangerous and interesting is the third of the new races. This so-called 'Cleo' race proved to be the first to break both resistance to the Nord-group and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1966
1966
1985
1985

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
Order By: Relevance
“…tritici) is closely associated with the phenomenon of continuous adaptation of the pathogen to its host, resulting in the appearance of new races . In The Netherlands, where the race population is determined annually, ten new races appeared during the period from 1955 to 1967 inducing epiphytotics on recently developed varieties that until then had been resistant (ZADOKS, 1961 ;UBELS et al ., 1965 ;STUBBS, 1967) . In 1968 another new race (race 60A) appeared, overcoming the resistance of the variety Flevina (Hope/Timstein//Heine's VII), which was one of the few remaining resistant varieties in The Netherlands .…”
Section: Introductionmentioning
confidence: 99%
“…tritici) is closely associated with the phenomenon of continuous adaptation of the pathogen to its host, resulting in the appearance of new races . In The Netherlands, where the race population is determined annually, ten new races appeared during the period from 1955 to 1967 inducing epiphytotics on recently developed varieties that until then had been resistant (ZADOKS, 1961 ;UBELS et al ., 1965 ;STUBBS, 1967) . In 1968 another new race (race 60A) appeared, overcoming the resistance of the variety Flevina (Hope/Timstein//Heine's VII), which was one of the few remaining resistant varieties in The Netherlands .…”
Section: Introductionmentioning
confidence: 99%
“…Since race 3/55 Opal was not able to infect Heines VII the isolates were tested on further supplementary cultivars. Results indicated that the isolates were similar to, but not identical with, race 3/55 Opal and 3/55 Cleo (Ubels et al, 1965) and the name 'race 3/55D' is therefore proposed for this new race. The reactions of race 3/55D, 3/55 Opal and 3/55 Cleo are given in Table 1 In 1967 an isolate was obtained from the resistant cultivar Maris Beacon at the Plant Breeding Institute, Cambridge.…”
Section: Resultsmentioning
confidence: 86%
“…Seventeen isolates were identified as being similar to race 3/55 Opal (Ubels et al, 1965) but with added virulence on Heines VII. Since race 3/55 Opal was not able to infect Heines VII the isolates were tested on further supplementary cultivars.…”
Section: Resultsmentioning
confidence: 99%